Gideon's sword - Preston, Douglas J.; Child, Lincoln (New York : Grand Central Pub., 2011)
"At age 12, Gideon Crew witnessed the brutal murder of his father. More than 20 years later, Gideon gets his revenge. But then a mysterious witness steps forward to confront Gideon on his crime--and offer him the chance of a lifetime"--Provided by publisher.
Keywords: Children of murder victims -- Fiction; Revenge -- Fiction; Mystery fiction